2005
DOI: 10.1007/s10444-004-1811-y
|View full text |Cite
|
Sign up to set email alerts
|

Introduction to the Web-method and its applications

Abstract: The Web-method is a meshless finite element technique which uses weighted extended B-splines (Web-splines) on a tensor product grid as basis functions. It combines the computational advantages of B-splines and standard mesh-based elements. In particular, degree and smoothness can be chosen arbitrarily without substantially increasing the dimension. Hence, accurate approximations are obtained with relatively few parameters. Moreover, the regular grid is well suited for hierarchical refinement and multigrid tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(50 citation statements)
references
References 18 publications
0
50
0
Order By: Relevance
“…Tensor product approximants can be used to generalize 1D methods such as B-Spline to multiple dimensions, but require structured grids. Recent examples include the References [6,18]. Subdivision approximations [15] can deal with unstructured data, but so far these approximants are theoretically well founded only in 2D.…”
Section: Sme Approximantsmentioning
confidence: 99%
“…Tensor product approximants can be used to generalize 1D methods such as B-Spline to multiple dimensions, but require structured grids. Recent examples include the References [6,18]. Subdivision approximations [15] can deal with unstructured data, but so far these approximants are theoretically well founded only in 2D.…”
Section: Sme Approximantsmentioning
confidence: 99%
“…The FCM system matrix is defined as 11) and the following is noted: 12) showing that the FCM norm of a function v h is equal to the energy norm of the corresponding vector y with system matrix A. Therefore the · 2 norm of A and its inverse according to (3.10) can be interpreted as the quotient of the FCM norm of a function and the Euclidean norm of the corresponding vector:…”
Section: Condition Numbers In Fcmmentioning
confidence: 99%
“…This can either be done by combining them with geometrically nearby functions [23,24] (as is also done in Web-splines [13,12]) or by simply excluding them from the approximation space, e.g., [7,29,33].…”
Section: Introductionmentioning
confidence: 99%
“…It is shown that the underlying problems related to the large number and mesh-dependence of design variables, the discretization of DBC as well as mesh updating can be completely avoided. According to [22][23][24][25][26], DBC is satisfied by penalizing displacement field with the weighting function defined by the LSF. This means that Dirichlet boundary shapes are described by implicit representations with continuous design variables independent of the mesh discretization.…”
Section: Introductionmentioning
confidence: 99%